Estimating the Impact on Water Quality under Alternate Land Use Scenarios: A Watershed Level BASINS-SWAT Modeling in West Georgia, United States - Bhattarai, Gandhi; Hite, Diane; Hatch, Upton (IntechOpen, 2011)
None